2022
DOI: 10.1186/s13045-022-01259-7
|View full text |Cite
|
Sign up to set email alerts
|

A new risk-assessment tool for venous thromboembolism in advanced lung cancer: a prospective, observational study

Abstract: Management of cancer-associated venous thromboembolism (VTE) is essential in treatment selection and cancer prognosis. However, to date, there is no method to assess the risk of VTE specifically associated with advanced lung cancer. Our aim was to create a new risk assessment scoring system that can predict the concomitant or incidence of VTE in advanced lung cancer. We used the dataset of 1008 patients with lung cancer in the Rising-VTE/NEJ037 study, of which 100 (9.9%) developed VTE. The items extracted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…Based on our analysis, the results showed that patients with adenocarcinoma have an approximately 3-fold higher risk of developing VTE than that of non-adenocarcinom apopulation. This result is consistent with the findings of previous studies (19,21,35). There is also clear evidence that patients with adenocarcinoma was associated with a markedly higher risk of VTE compared with other pathological types (8,35).…”
supporting
confidence: 94%
See 3 more Smart Citations
“…Based on our analysis, the results showed that patients with adenocarcinoma have an approximately 3-fold higher risk of developing VTE than that of non-adenocarcinom apopulation. This result is consistent with the findings of previous studies (19,21,35). There is also clear evidence that patients with adenocarcinoma was associated with a markedly higher risk of VTE compared with other pathological types (8,35).…”
supporting
confidence: 94%
“…According to the results of the logistic regression analyses, we established a simplified eleven-variables nomogram model, which contains four clinical variables(BMI, histology, clinical stage and CVC history), four biomarkers(D-dimer, PT, Fbg and TG), oncogenic abnormalities(ROS-1 rearrangement) and history of previous radiotherapy and chemotherapy treatment. Many of the risk factors of cancer-associated VTE identified in this analysis, particularly in lung cancer, were mostly consistent with those of the previous literatures (18)(19)(20)(21). Among the numerous risk factors, it is widely accepted that higher BMI were patient-related risk factors related to VTE.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…However, the histology of lung cancer was not considered. A number of studies in the literature suggest that patients with adenocarcinoma (with or without VTE) may have a worse outcome than those with squamous or other types of lung cancer [ 1 , 3 , 13 , 14 , 15 , 16 ]. Better knowledge of the potential impact of lung cancer histology on outcome might likely help to design better therapeutic strategies for patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%